2020
DOI: 10.1111/ctr.14180
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from calcineurin inhibitors to sirolimus in transplant‐associated thrombotic microangiopathy

Abstract: Transplant‐associated thrombotic microangiopathy (TA‐TMA) is a specific complication of allogeneic hematopoietic cell transplantation with a multifactorial etiology. There is little evidence published regarding the efficacy and factors influencing the outcome of substitution of calcineurin inhibitors (CNIs) with other agentsas a widely accepted practice in this disorder; however, there are limited data on the options for immunosuppression manipulation (ISM). In our study, we retrospectively analyzed outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The two main groups of immunosuppressants used in all forms of transplantation, i.e. , calcineurin inhibitors (CNIs) and mammalian target of rapamycin (mTOR) inhibitors (mTORi) such as sirolimus, can both trigger the development of PT-TMA[ 39 , 40 ]. The etiologic role of CNIs in causing PT-TMA is well established.…”
Section: Etiology Of Pt-tmasmentioning
confidence: 99%
See 1 more Smart Citation
“…The two main groups of immunosuppressants used in all forms of transplantation, i.e. , calcineurin inhibitors (CNIs) and mammalian target of rapamycin (mTOR) inhibitors (mTORi) such as sirolimus, can both trigger the development of PT-TMA[ 39 , 40 ]. The etiologic role of CNIs in causing PT-TMA is well established.…”
Section: Etiology Of Pt-tmasmentioning
confidence: 99%
“…The etiologic role of CNIs in causing PT-TMA is well established. However, the role of mTOR inhibitors is still largely controversial[ 40 ]. In vitro studies have suggested that sirolimus causes endothelial cell (EC) injury only when used in combination with tacrolimus.…”
Section: Etiology Of Pt-tmasmentioning
confidence: 99%
“…Treating infections and aGVHD may decrease the severity of TMA by dampening the feedback loop of endothelial damage and inflammation. Removing CNIs may improve TA-TMA, by diminishing the direct toxic effects on the endothelium (studied in vitro) [29][30][31]. However, this strategy is complicated…”
Section: Current Management Paradigmmentioning
confidence: 99%
“…Also, the different centers are testing other type of agents for GVHD prophylaxis instead of CNIs, with effects on survival outcomes. In our single-center analysis, substitution of CNIs by sirolimus in severe GVHD proved to be superior to steroids [53]. Novel agents, like JAK inhibitors, might also facilitate sufficient GVHD control instead of CNIs without additional endothelial damage [54].…”
Section: Treatment Of Transplant-associated Thrombotic Microangiopathymentioning
confidence: 99%